DETERMINANTS OF POVERTY IN EAST KALIMANTAN: A PANEL DATA APPROACH - Muhammad Fauzan Fadhlani; Tony Irawan; Dominicus Savio Priyarsono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the effect of per capita gross domestic product (GDP), poverty line, and open unemployment rate on the number of poor people in East Kalimantan using panel data regression analysis. The data used is secondary data from 2015-2022. The results of the analysis show that the best model in this case is the random effects model. All the dependent variables simultaneously have a significant effect on the number of poor people. Partially, GRDP per capita and the open unemployment rate have no significant effect. Meanwhile, the poverty line has a significant positive effect on the number of poor people in East Kalimantan